Georgian Traces in the History of the Chuvash - Salmin Anton K. (Oriental Studies, 2023)
The paper deals with the Transcaucasian prehistoric period in the history of the ancestors of the Chuvash people. Goals. The study aims to identify and analyse the sources and literature on the topic relating to events of the 7th to 1st centuries BC. Materials and methods. The work employs a complex approach to the examination of the material, which made it possible to analyse the sources and the thoughts of predecessors consistently and systematically. The study focuses on works of historians, ethnographers and linguists about the ethnic groups that previously inhabited and now inhabit the areas to the south of the Greater Caucasus. The sources that proved important include the works by such historians as Herodotus (5th century BC), Apollonius of Rhodes (3rd c. BC), Pseudo-Orpheus (4th c. AD), Priscus Panionensis (5th c.), Menander Protector and Stephanus of Byzantium (both 6th c.). The paper also makes use of some pronouncements by such remarkable researchers as Andrey Golovnev, Sergey Arutyunov, Alikber Alikberov, Nicholas Berdzenishvili, Vera Budanova, Murtazali Gadzhiev, and David Muskhelishvili. Results. Impartial investigation shows that the ethnonym of the Chuvash has undergone a lengthy course of transformation through history in the form of Savir (Saspir/Sapir, Savar, Sabir) → Suvar (Suvas, Suvan) → Suvash → T’šăvaš (Chuvash). As far back as the 7th century BC, to the southeast of Colchis a large confederation of tribes headed by the Saspirs came into being. The study reveals and confirms traces in the pre-history of the distant ancestors of the Chuvash that are shared with the peoples of Georgia. In the period under examination, the historical forerunners of the Chuvash lived in a territory between Media and Colchis, between the Medes and the Colchians. In the 3rd century BC and the 3rd century AD, they were recorded to inhabit the Chorokh River valley. Alongside historical events, the publication traces ethnographic parallels with the ancient Georgian peoples and some shared elements of vocabulary.